Upaya Peningkatan Hasil Output Produksi pada Departemen A di PT. X - Angeline Soegiarto (Jurnal Titra, 2020)
PT. X is a subsidiary of one of the largest wood manufacturers in Indonesia.The main complication is that the production output of the Packing Department fell below the set target. The purpose of this research is to determine the various factors that can impede the production causing it not to reach the target, and regulate preventative ways so the situation will not be repeated in the future. The methods used are field observation, interview with the A Department coordinator of the company, and Stopwatch Time Study for timing. Calculated using standard time, the capacity of production for Y product supposed to reach 51,1197825 containers. However, the actual output was only 23,07792208 containers, whereas the production target was as high as 62 containers. The reasons why the demand was not fulfilled were that the target was greater than the production capacity and actual output was less than the production capacity, which were caused by the delay in input and processes from the B Department and A Department, respectively. A few proposed solution are adding units for the longest processing procedure, line balancing, seeking local suppliers, and double-checking the product posters’ design before being printed and handed to QC buyer.